GaNAs/InGaAs Superlattice Solar Cells with High N Content in the Barrier Grown by All Solid-State Molecular Beam Epitaxy - 卢建娅 郑新和 王乃明 陈曦） 李宝吉 陆书龙 杨辉 (Chinese physics letters, 2015)
We demonstrate nearly i e V GaN0.03As0.97 /In0.09 Ga0.91As strain-compensated short-period superlattice solar cells by all solid-state molecular beam epitaxy. The optimal period thickness for the superlattice growth is achieved to realize high structural quality. Meanwhile, the annealing conditions are optimized to realize a pho- toluminescence （PL） at a low temperature. However, no PL signal is detected at room temperature, which could be reflected by a lower open-circuit voltage of the fabricated devices. The GaN0.03As0.97/In0.09Ga0.91As super- lattice solar cells show a reasonably-high short-circuit current density （Jsc） of over lOmA/cm2. Eurthermore, a concentration behavior is measured, which shows a linear relationship between Jsc and concentration ratios. The extrapolated ideality factor and saturated current density by the concentration action are in good agreement with that extracted by the dark case of the p-i-n diodes.